The Fraud Hexagon Model and Corporate Governance Moderation in the Investigation of Financial Statement Fraud - Enggar Diah Puspa Arum; Wahyudi, Ilham (Dinasti Publisher, 2024)
Financial statement fraud is fraud committed by management in the form of misstatements of financial information that can harm other parties for personal or certain group interests. In recent years, the theory of financial statement fraud has developed, starting with the triangle, diamond, pentagon, and finally hexagon theories. The hexagon theory is a development of the previous theory with the components of stimulus, capability, collusion, opportunity, rationalization, and ego. The effect of the Hexagon Theory component on financial statement fraud is investigated in this study, with corporate governance serving as a moderating variable. This quantitative research was developed by observing 235 sets of data obtained from annual reports of public companies in the property and real estate sectors listed on the Indonesia Stock Exchange for the 2016–2020 period and analyzing them using a panel data regression model processed with the EViews program. The results of the study prove that only the stimulus component, as measured by financial targets, and external pressure affect financial statement fraud. Furthermore, corporate governance has been shown to moderate the relationship between financial statement fraud and stimulus, opportunity, rationalization, and ego.